Radial Head Lag: A Possible Biomechanical Mechanism for Osteochondritis Dissecans of the Capitellum in Baseball Pitchers. Issue 12 (October 2021) - Rotman, Dani; Kwak, Jae-Man; Rojas Lievano, Jorge; Hooke, Alexander; Camp, Christopher L.; Fitzsimmons, James S.; O'Driscoll, Shawn W.
Background: Osteochondritis dissecans (OCD) of the capitellum is common in throwing athletes and is believed to result from repetitive overloading on the radiocapitellar (RC) joint, although the cause and mechanism remain unclear. The torsional forces (moments) generated by the triceps during elbow extension pull only on the ulna; therefore, the radial head moves passively across the capitellum and is effectively "dragged along" by the ulna. Any laxity in the proximal radioulnar joint could lead to asynchronous motion between the radius and ulna, resulting in the radial head lagging behind the coronoid and possibly malarticulating with the capitellum during such motion. Hypothesis: Radial head motion on the capitellum lags behind ulnohumeral joint motion during simulated throwing. Study Design: Controlled laboratory study. Methods: A total of 8 cadaveric elbows were tested under simulated throwing, including active extension of the elbow generated by pulling of the triceps under valgus stress, as well as during passive extension under valgus stress to serve as a reference. Ulnohumeral motion was tracked using a video camera. Radial head motion was tracked using an intra-articular, thin-film pressure sensor mounted on the capitellum, and the longitudinal movement of the center of force (COF) of the radial head was measured. Radial head motion was compared between passive and active motion for each 10° of elbow extension from 90° to 20°. Results: Elbow motion during simulated active extension reached an angular velocity of 366 deg/s. Radial head motion during simulated active extension significantly lagged compared with its motion during passive extension at every elbow extension angle examined between 70° and 20° ( P < .001). The maximal lag reached a mean of 4 mm (range, 2-7 mm). In other words, RC and ulnohumeral motion were asynchronous during simulated throwing. Conclusion: This study describes a novel phenomenon: motion of the radial head across the capitellum during rapid extension, such as in baseball pitching, lags behind that seen during passive elbow motion. According to a new proposed theory of OCD lesion development, this lag should result in RC incongruency and elevated shear forces on the capitellum due to edge loading. Clinical Relevance: We propose a new biomechanical explanation for OCD of the capitellum in baseball pitchers: radial head lag. Understanding this process is the first step in efforts to prevent this common injury.